PENGARUH KOMPOSISI LIMBAH SABUT KELAPA DAN KOTORAN SAPI TERHADAP KARAKTERISTIK BRIKET SEBAGAI BAHAN BAKAR ALTERNATIF - Muhammad Fithroni Ramadhani; Sarita Oktorina; Erry Ika Rhofita (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
Biomass residue plays an essential role in rural communities due to its abundance, affordability, and renewable nature. This study examined the influence of cow dung (KS) and coconut husk (SK) composition and particle size on briquette properties, including density, moisture, ash content, and calorific value. Briquettes were produced using three compositions (80KS20SK, 70KS30SK, and 50KS50SK) and two particle sizes (40 and 80 mesh) under a densification pressure of 10 MPa. The 70KS30SK briquette with 80 mesh particles showed the highest density (≈312.38 kg/m³) and the lowest moisture content (≈1.98%). Smaller particle size improved bonding and reduced pore formation, enhancing density. Meanwhile, the 50KS50SK mixture produced briquettes with higher calorific value (13.05–14.36 MJ/kg) and lower ash content (17.16–21.59%) than other samples, indicating that composition affects energy content and residue formation. However, the calorific value and ash content did not meet the SNI 1683:2021 standards. Overall, the results highlight the potential of cow dung–coconut husk briquettes as a sustainable waste-to-energy option for rural applications.